The Effect of the Entry of Private Firms in the Upstream of the Industry Chain on the Privatization of State-owned Firms - Hamideh Esfahani; Mohammad Alikhani; Mehdi Fadaee (برنامه‌ریزی و بودجه, 2023)
This article examines the possibility of improved social welfare as a result of the entry of a new private firm, domestic or foreign, into the upstream industry, in a situation where the upstream industry had a monopoly structure with the existence of a single government firm. A public firm can be privately or publicly managed, that is to say that it aims to either maximize profits or social welfare. The results of this study show that while in the monopoly structure, the privatization of a state-owned enterprise is an ineffective policy in terms of social welfare, the increase in competition leads to the justification of privatization, provided that the technology of the new domestic enterprise is more efficient than the state-owned enterprise within a certain range. If the new domestic enterprise is much more efficient than the state-owned enterprise or has a relatively similar technology, it will still be a suboptimal policy to privatize the state-owned enterprise. On the other hand, if the new entrant is a foreign company, the privatization of the state-owned company will be the optimal policy in a situation where the foreign company has a much more efficient technology than the state-owned company.